Bahasa Inggris - Agus Purnomo; Atika Zahra Maulida; Muhammad Arsyad Al Banjari Banjarmasin (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
Hajj savings is a product owned by Bank Syariah Indonesia cab Tanjung. Through hajj savings products, Bank Syariah Indonesia collects Hajj funds managed and distributed through sukuk investments (corporate, state, and regional), deposits, sharia stocks, and mutual funds. In 2021, the collection of Hajj funds had increased every year by 35% of the amount of IDR 17,869,510,000,000 hajj funds collected through Bank Syariah Indonesia distributed to state sukuk products to obtain profit or income. So the manager explains that the Hajj fund will be distributed in the type of business, time, and profit sharing. This research method uses a qualitative approach by conducting interviews with the management and Hajj at Bank Syariah cab Tanjung by applying the mudharabah mutlaqah agreement in the distribution and distribution of revenue sharing of the Hajj fund. In determining informants using the purposive sampling method, which consists of 5 informants who will be interviewed about the distribution and calculation of the profit sharing of Hajj funds. In 2020 the Hajj fund collected from the public amounted to IDR 17,890,723,000, - so that Islamic banks as hajj fund managers will distribute the Hajj funds in the form of investment as the following: money market, capital market, construction of facilities and infrastructure, deposits and national sharia valuable certificates (SBSN). Islamic banks will provide a monthly profit sharing of 4%, distributed to Hajj savings customers.